Numerical analysis of interlaminar stresses in open-hole laminates under compression. (1st June 2019) - Solis, A.; Sanchez-Saez, S.; Martinez, X.; Barbero-Pozuelo, E.
Abstract: In this paper, the interlaminar stresses in open-hole laminates subjected to compressive loads are analysed using a numerical model. This model implements the Serial/Parallel Mixing Theory (S/PMT) and a Continuum Damage Mechanics (CDM) approach. The S/PMT estimates the global stiffness in the laminate from fibre and matrix properties. The CDM approach models the damage initiation due to fibre microbuckling. The global response estimated by the model was verified with experimental data from the literature. The model predicts that the damage initiates in the laminate middle-plane where the thickest block of plies oriented in the load direction is located, and progressively propagates to the nearest block of layers with the same orientation. Two laminate stacking sequences were analysed. The interlaminar stresses around the hole presented symmetry with respect to the load direction and the perpendicular axis, being located the maximum and minimum values in different angular positions for each stress component and laminate.